The Biomechanical Effect of the Sagittal Split Ramus Osteotomy on the Temporomandibular Joint: Current Perspectives on the Remodeling Spectrum - Verhelst, Pieter-Jan; Van der Cruyssen, Fréderic; De Laat, Antoon; Jacobs, Reinhilde; Politis, Constantinus (Frontiers in Physiology, 2019)
The sagittal split ramus osteotomy is a key approach for treating dentofacial deformities. Although it delivers excellent results, the sagittal split ramus osteotomy is believed to induce stress to the temporomandibular joint. Potential stress inducers could be classified as per- and postoperative factors resulting in an inflammatory response and molecular cascades, which initiates physiological remodeling. Occasionally, this process exceeds its capacity and causes pathological remodeling, through either degenerative joint disease or condylar resorption. Hard evidence on how orthognathic surgery causes inflammation and how this inflammation is linked to the spectrum of remodeling remains scarce. Current concepts on this matter are mainly based on clinical observations and molecular mechanisms are extrapolated from fundamental research in other body parts or joints. This perspective study provides an overview of current knowledge on molecular pathways and biomechanical effects in temporomandibular joint remodeling. It provides research directions that could lead to acquiring fundamental evidence of the relation of orthognathic surgery and inflammation and its role in remodeling. Performing osteotomies in animal models and identifying inflammatory mediators as well as their effect on the joint seems promising. Patients affected by pathological remodeling can also provide samples for histological as well as molecular analysis. Individual susceptibility analysis by linking certain suspect phenotypes to genetic variation could identify the cause and molecular pathway responsible for degenerative joint disease and condylar resorption, ultimately leading to clinically applicable treatment and prevention strategies.